(untitled) (Cardiovascular Journal, 2011)
Intensive Care Unit (ICU) is the most vulnerable area in the hospital premises. Hospital acquired infections in critically ill patients as well as of transmission of infections from a patient to another patient or to the health care workers or vice versa can occur in ICU. ICUs combine physicians, nurses and allied health professionals to manage patients with life threatening single or multiple organ system failure, including stabilization after surgical interventions. It is a continuous management including monitoring, diagnosis, and support of failing vital functions as well as the treatment of the underlying disease. Here we have to discuss the source of infection and their effective control measurement in intensive care unit. Ventilator associated pneumonia (VAP) as well with other sources is most common nosocomial infection having 33% mortality in ICU. Key words: Intensive care unit, Pneumonia, ventilator pneumonia DOI: http://dx.doi.org/10.3329/cardio.v1i1.8218 Cardiovasc. j. 2008; 1(1) : 78-80